2003
DOI: 10.1021/ja034500e
|View full text |Cite
|
Sign up to set email alerts
|

σσ* Transition in anti,cisoid Alternating Oligosilanes:  Clear-Cut Evidence for Suppression of Conjugation Effect by a cisoid Turn

Abstract: On the basis of the UV absorption spectra of the anti,cisoid alternating oligosilanes, the first experimental clear-cut evidence was presented for the generally accepted idea that the sigma conjugation in polysilanes does not effectively extend through a tetrasilane fragment with a small dihedral angle such as a cisoid turn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 22 publications
2
59
0
Order By: Relevance
“…These findings clearly revealed that σ-conjugation in polysilanes is effectively extended by anti or deviant conformations, while conformations with small dihedral angles such as syn, cis or gauche do not contribute to the extent of σ-conjugation [102]. Similar conclusions can be drawn for polysilane dendrimer, even though the redundancy of silicon chains and the steric strain causes a variety of more or less flexible conformers to be formed, each contributing differently to the extent of σ-conjugation along the silicon backbone.…”
Section: Conformational Effectsmentioning
confidence: 90%
See 1 more Smart Citation
“…These findings clearly revealed that σ-conjugation in polysilanes is effectively extended by anti or deviant conformations, while conformations with small dihedral angles such as syn, cis or gauche do not contribute to the extent of σ-conjugation [102]. Similar conclusions can be drawn for polysilane dendrimer, even though the redundancy of silicon chains and the steric strain causes a variety of more or less flexible conformers to be formed, each contributing differently to the extent of σ-conjugation along the silicon backbone.…”
Section: Conformational Effectsmentioning
confidence: 90%
“…It was shown theoretically and experimentally that the σ-σ* absorption peak shifts dramatically to the red as the SiSiSiSi dihedral angle, ω, is increased from 0° to 180° [99][100][101][102][103][104]. This effect was explained by 1,4-orbital interactions (β vic ), being most effective (maximum orbital overlap) in the HOMO (σ-type orbital) of a syn-conformer, while not present in an anti-conformer.…”
Section: Conformational Effectsmentioning
confidence: 99%
“…[49] The right-hand side of Figure 2s erves only for highlighting the contrast between s-delocalized and a s-localized behavior and will be dealt with in more detail elsewhere. It displays the reported UV absorption spectra of the alternating polycyclic oligosilanes all-[c]-2 [4] to all-[ca]-2 [10], [21] again with arandomly distributed helicity sense, in which the purpose of the additional alkane chains is to impose on the silicon backbone the geometry of the desired conformation. Along with these spectra, Figure2 shows the resultso fT D-DFT/TZ calculations for the permethylated linear analogs of these polycyclic oligomers ([c]-1 [4] to all-[ca]-1 [10] in Figure 1, with uniform helical sense).…”
Section: (Iii) S-delocalized and S-localized Conformersmentioning
confidence: 99%
“…2729 In most cases, the thermodynamically favored conformations with a large number of transoid dihedral angles become predominant at lower temperatures 30. These conformers generally show the effects of σ delocalization most strongly and absorb at longer wavelengths, whereas the smallest SiSiSiSi dihedral angles act as defects and hinder an effective display of the effects of conjugation 31. 32…”
Section: Introductionmentioning
confidence: 99%